Two new species of Stigmaeidae (Acari: Trombidiformes: Rhaphignathoidea) from Brazil - Paktinat-Saeij, Saeid; Barroso, Geovanny; Cruz, Wilton Pires Da (Zootaxa, 2017)
Two new species of Stigmaeidae, Agistemus rodriguezi Paktinat-Saeij & Cruz sp. nov. and Eryngiopus moraesi Paktinat-Saeij & Barroso sp. nov. are described and illustrated on the basis of adult specimens from northern Brazil.